2010
DOI: 10.4132/koreanjpathol.2010.44.1.106
|View full text |Cite
|
Sign up to set email alerts
|

Fine Needle Aspiration Cytology of Langerhans Cell Histiocytosis of Mandible - A Case Report -

Abstract: We present a case of mandibular involvement with Langerhans cell histiocytosis (LCH), diagnosed by ultrasound-guided aspiration and subsequently confirmed by incisional biopsy and immunohistochemistry in an eight-year-old boy. The cytologic findings included the presence of characteristic Langerhans cells of both mononucleate and multinucleate form. Diagnostic confirmation was obtained by immunopositivity for S-100 protein and CD1a of Langerhans histiocytes on paraffin-embedded sections obtained during incisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Lee et al . [ 5 ] reported a case of LCH in the mandible diagnosed with fine needle aspiration cytology and indicated that the smear revealed high cellularity, and that the LCs had abundant vacuolated cytoplasm with round or occasionally folded nuclei. The LC nuclei showed a fine granular chromatin pattern with prominent nucleoli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al . [ 5 ] reported a case of LCH in the mandible diagnosed with fine needle aspiration cytology and indicated that the smear revealed high cellularity, and that the LCs had abundant vacuolated cytoplasm with round or occasionally folded nuclei. The LC nuclei showed a fine granular chromatin pattern with prominent nucleoli.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] reported a case of LCH in lymph nodes using aspiration cytology similar to the case reported by Lee et al . [ 5 ]. In their study, the LCs had wrinkled or grooved nuclei with thin nuclear membranes and a delicate chromatin pattern.…”
Section: Discussionmentioning
confidence: 99%